Financial System Development and Economic Growth in Sub-Saharan Africa (2016)
This paper contributes to the age-old debate on the link between financial development and economic growth by examining the role of monetary policy. There is a possibility that monetary policy enhances financial system performance with attendant impact on growth. To unveil this influence, this paper employs fixed effects and System GMM on data from 28 sub-Saharan African countries over the period 1996 to 2014. Results from the baseline estimation using fixed effects indicate that financial development indicators are negatively and significantly associated with growth for two of the three measures used (LGDP and PGDP), while money growth is positively related albeit insignificantly. The results largely remain the same on interaction with money growth. The coefficients of the interactive terms though largely negative are, however, not significant. The results from System GMM presents a different outcome. First, all measures of financial development turn out positive (except BBD) and insignificant. Financial development equally turns negative but insignificant after interacting with money growth. Overall, monetary policy measures, together with their interactions with financial development indicators, show up as weak growth predictors if not dampening, suggestive of the plausible independence of the nexus on the actions of monetary authorities in these countries.